2020
DOI: 10.1002/ptr.6818
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents, clinical efficacy and molecular mechanisms of the ethanol extract of Abelmoschus manihot flowers in treatment of kidney diseases

Abstract: Abelmoschus manihot, also called as “Huangkui” in Chinese, is an annual flowering herb plant in the family of Malvaceae. As a traditional Chinese medicine, the ethanol extract of the flower in Abelmoschus manihot is made as Huangkui capsule and has been used for medication of the patients with kidney diseases. Its efficacy in clinical symptoms is mainly improving renal function and reducing proteinuria among the patients with chronic kidney disease, diabetic kidney disease or IgA nephropathy. The possible mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Medicus (A. manihot), was approved by China's State Food and Drug Administration in 1999 for treating chronic nephritis. Studies have confirmed the renal protective effect of the Huangkui capsule in vivo, in vitro, and clinically [105,140]. Flavonoids, the main chemical component of the Huangkui capsule, can be converted into glucuronic acid-sulfate conjugates in vivo, which may contribute to the nephroprotective effects [141].…”
Section: Huangkui Capsulementioning
confidence: 80%
“…Medicus (A. manihot), was approved by China's State Food and Drug Administration in 1999 for treating chronic nephritis. Studies have confirmed the renal protective effect of the Huangkui capsule in vivo, in vitro, and clinically [105,140]. Flavonoids, the main chemical component of the Huangkui capsule, can be converted into glucuronic acid-sulfate conjugates in vivo, which may contribute to the nephroprotective effects [141].…”
Section: Huangkui Capsulementioning
confidence: 80%
“…The total flavones of Abelmoschus manihot (TFA) are the main components of Huangkui capsule (HKC; the local name in China), which is a modern Chinese patented medicine preparation extracted from Abelmoschus manihot (AM). This preparation has been approved by the China State Food and Drug Administration (Z19990040) for the treatment of CKD and has been used over the past two decades (Zhang et al, 2014;Li et al, 2020). Clinical evidence in China has suggested that HKC (at the safe and effective dose of 7.5 g/kg/day) can reduce urinary albumin in CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN), 1 of the major complications of diabetes mellitus, [ 1 , 2 ] has become a threat to human health and mortality. [ 3 , 4 ] DN shows progressive renal damage over several years and involves many pathological changes: excessive deposition of extracellular matrix, glomerulosclerosis and renal interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%